(untitled) (Academicia Globe: Inderscience Research, 2021)
The value and importance of moral culture, as well as morality, is manifested in the behavior, communication and activities of people, in their open worldview, in their personal example. Theoretically correct understanding of the essence of the concept of moral culture, its significant role in the cultural development of society and the formation of the spiritual world of the individual can be a necessary basis for this. The article elaborates on the importance of developing the moral culture of university students.